FINANCIAL DISTRESS PREDICTION OF FINANCIAL SECTOR SERVICE COMPANIES ON INDONESIAN STOCK EXCHANGE USING COX PROPORTIONAL HAZARD - Dwi Putra, Candra Yanuar; Fatekurohman, Mohamat; Anggraeni, Dian (PATTIMURA UNIVERSITY, 2022)
A company that cannot compete with its competitors is likely to experience financial difficulties or commonly referred to as financial distress. Financial distress is a stage of a decline in the company's financial condition or a situation of financial difficulty that occurred before the company went bankrupt. This study aims to determine the factors that can predict a company experiencing financial distress. The factors suspected in this study include leverage, profitability, company size, free cash flow and sales growth. The method used is the Cox Proportional Hazard model. The research data is data on financial sector service companies listed on the Indonesia Stock Exchange (IDX) for 5 years of observation, namely from 2016 to 2020. Based on the results of the analysis of financial distress predictions using the Cox Proportional Hazard model, it is found that the factors that have a significant effect on predicting companies experiencing financial distress are: financial distress, namely profitability and company size.